Pengaruh Jumlah Unit Usaha, Investasi, dan Nilai Produksi terhadap Penyerapan Tenaga Kerja pada Industri Kecil di Kota Banjarmasin - Rahmadiannor, Fahlefi; Chandriyanti, IK (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study aims to measure the effect of the number of business units, investment, and production value on the workforce in small industries in Banjarmasin City. The scope of the research is labor in small enterprises in Banjarmasin City. The type of research used in measuring delivery in small enterprises in the City of Banjarmasin is quantitative research; quantitative data and objective statistics are calculated scientifically from data obtained from the Central Statistics Agency of Banjarmasin City. The results of this study are that there is a joint influence between the number of business units, investment, and production value on labor in small industries in Banjarmasin City. At the same time, the number of business units in small enterprises in Banjarmasin City partially has a significant influence; in line with the results of the test, the most dominant variable influencing is the number of business units in the workforce in small industries in Banjarmasin City.